2017
DOI: 10.56093/ijans.v87i2.67704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium-yeast feeding on amelioration of simulated heat stress and reproductive performance in Malpura ewe under semi-arid tropical environment

Abstract: The present study was carried out for 35 days to assess the effect of selenium (Se)-yeast feeding on amelioration of simulated heat stress and reproductive performance of sheep. Twelve adult Malpura ewes were divided into two groups viz., G1 (n=6, control) and G2 (n=6, Se-yeast supplemented). The ewes of G2 were provided with Se at 0.3 mg/kg feed dry matter (DM) through Se-enriched yeast (Saccharomyces cerevesiea). The animals were stall fed individually with a diet consisting of 70% roughage (Cenchrus ciliari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Similarly, when the temperature decreased in the EG, we observed no differences between groups (e.g., on days 12 and 13, where we observed that the unshaded pen had no effect on RF). Several authors (Sayer et al, 1979;Al-Haidary, 2004;Chauhan et al, 2014;Indu et al, 2014;Sejian et al, 2014;De et al, 2017;Li et al, 2018) have generated stressful conditions in climatic chambers with high temperatures and relative temperatures to simulate environmental conditions. The physiological variables were greater in the RT and RF groups than in the control group in each experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, when the temperature decreased in the EG, we observed no differences between groups (e.g., on days 12 and 13, where we observed that the unshaded pen had no effect on RF). Several authors (Sayer et al, 1979;Al-Haidary, 2004;Chauhan et al, 2014;Indu et al, 2014;Sejian et al, 2014;De et al, 2017;Li et al, 2018) have generated stressful conditions in climatic chambers with high temperatures and relative temperatures to simulate environmental conditions. The physiological variables were greater in the RT and RF groups than in the control group in each experiment.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of increases in RT in hair and indigenous sheep during stressful environmental conditions or in climatic chambers with high temperatures or high THI. (Sawyer et al, 1979;Al-Haidary, 2004;Sejian et al, 2014;Chauhan et al, 2014;Indu et al, 2014;De et al, 2017;Li et al, 2018;Gomez-Guzman et al, 2021). In our study, we did not find a greater increase in RT between the CG and EG.…”
Section: Discussionmentioning
confidence: 99%